2022
DOI: 10.1088/1361-6463/ac7f67
|View full text |Cite
|
Sign up to set email alerts
|

Transient characteristics of β-Ga2O3 nanomembrane Schottky barrier diodes on various substrates

Abstract: In this paper, transient delayed rise and fall times for beta gallium oxide (β-Ga2O3) nanomembrane (NM) Schottky barrier diodes (SBDs) formed on four different substrates (diamond, Si, sapphire, and polyimide) were measured using a sub-micron second resolution time-resolved electrical measurement system under different temperature conditions. The devices exhibited noticeably less-delayed turn on/turn off transient time when β-Ga2O3 NM SBDs were built on a high thermal conductive (high-k) substrate. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Experiments have demonstrated that integrating β-Ga 2 O 3 heterostructures onto highthermal-conductivity substrates can effectively enhance device heat dissipation. One of the most effective solutions is to utilize diamond substrates to grow Ga 2 O 3 thin films, due to the excellent thermal conductivity of diamond, which can effectively dissipate heat [254][255][256][257][258]. However, due to lattice mismatch, the quality of β-Ga 2 O 3 films grown by heteroepitaxy is often poor, limiting device performance [259][260][261].…”
Section: Surge Current Ruggedness and Thermal Managementmentioning
confidence: 99%
“…Experiments have demonstrated that integrating β-Ga 2 O 3 heterostructures onto highthermal-conductivity substrates can effectively enhance device heat dissipation. One of the most effective solutions is to utilize diamond substrates to grow Ga 2 O 3 thin films, due to the excellent thermal conductivity of diamond, which can effectively dissipate heat [254][255][256][257][258]. However, due to lattice mismatch, the quality of β-Ga 2 O 3 films grown by heteroepitaxy is often poor, limiting device performance [259][260][261].…”
Section: Surge Current Ruggedness and Thermal Managementmentioning
confidence: 99%